2007
DOI: 10.1039/b612489e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental determination of the electronic structure of V2O5, reduced V2O5−xand sodium intercalated NaV2O5

Abstract: In this work the electronic structure of V(2)O(5), reduced V(2)O(5-x) (V(16)O(39)) and sodium intercalated NaV(2)O(5) has been studied by both theoretical and experimental methods. Theoretical band structure calculations have been performed using density functional methods (DFT). We have investigated the electron density distribution of the valence states, the total density of states (total DOS) and the partial valence band density of states (PVBDOS). Experimentally, amorphous V(2)O(5) thin films have been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 68 publications
8
56
0
Order By: Relevance
“…With increasing temperature V 3+ species were gradually created. The latest results obtained by resonant photoelectron and X-ray absorption near edge structure spectroscopies are in accord with previous findings [80]. Note that if singly coordinated oxygen atoms are removed, the presence of V 4+ species indicates that the two electrons left in the system per defect created do not remain together at the V atom to which the removed oxygen was initially bonded, as discussed below (Sect.…”
Section: Experimental Findings On Oxygen Defectssupporting
confidence: 90%
See 3 more Smart Citations
“…With increasing temperature V 3+ species were gradually created. The latest results obtained by resonant photoelectron and X-ray absorption near edge structure spectroscopies are in accord with previous findings [80]. Note that if singly coordinated oxygen atoms are removed, the presence of V 4+ species indicates that the two electrons left in the system per defect created do not remain together at the V atom to which the removed oxygen was initially bonded, as discussed below (Sect.…”
Section: Experimental Findings On Oxygen Defectssupporting
confidence: 90%
“…Furthermore, Sauer and Döbler performed 2L clusters studies using PBE and B3LYP [22] and found a corresponding shrinkage from 3.21 to 1.86 Å and expansion from 1.58 to 1.69 Å with B3LYP. Interlayer bond formation upon creation of isolated vanadyl oxygen defects in the bulk was also reported [80,81,133]. Note that the atomic displacements due to isolated O 1 vacancies occur at all defect sites upon increasing the defect concentration, as shown by Ganduglia-Pirovano and Sauer [23].…”
Section: Structure Relaxation and Electronic Structuresupporting
confidence: 52%
See 2 more Smart Citations
“…After background subtraction the VB photoemission spectrum for SrRuO 3 can be calculated for a particular photon energy using the following approximate expression (DOS approximation): [40][41][42] …”
Section: B Resonant Ups Data Normalizationmentioning
confidence: 99%